Health Taxes: Policy And Practice - Jeremy A. Lauer; Franco Sassi; Agnès Soucat; Angeli Vigo (World Scientific Publishing Europe Ltd, 2023)
Virtually all fiscal measures influence people's health, through their impacts on behaviour, consumption, income and wealth. A narrow subset of fiscal measures, however, can be more directly aimed at improving health by targeting behaviours and risks that are known to be strongly associated with health outcomes. The purpose of this book is to discuss the subject of these measures, which we define as 'health taxes'. The book aims to enumerate key health taxes of interest, explore their positive and negative effects, and how these effects are influenced by the design of these taxes and the context in which they are applied. We ask how and where they can be implemented. Critically, we build an argument throughout the book for why policymakers across government should care about health taxes.
Keywords: 330; Economics & Finance; Health Economics